2017
DOI: 10.1158/2326-6066.cir-16-0114
|View full text |Cite
|
Sign up to set email alerts
|

Rational Selection of Syngeneic Preclinical Tumor Models for Immunotherapeutic Drug Discovery

Abstract: (word count: 239):Murine syngeneic tumor models are critical to novel immuno-based therapy development but the molecular and immunological features of these models are still not clearly defined. The translational relevance of differences between the models is not fully understood, impeding appropriate preclinical model selection for target validation, and ultimately hindering drug development. Across a panel of commonly-used murine syngeneic tumor models, we showed variable responsiveness to immunotherapies. W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
403
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 335 publications
(436 citation statements)
references
References 55 publications
32
403
1
Order By: Relevance
“…Our data show that even non-activated Tcells are more motile than B-cells. 75 Our study thus underlines a number of previously under-appreciated metabolic distinctions between B-and T-cells that are likely to be of substantial functional relevance in disease microenvironments. Aerobic glycolysis, and not mitochondrial ATP, has been found to be essential for motility in other cell types as well, and has been associated with fluctuations in membrane pump.…”
Section: B-cells In Other Words B-cells Show a Globally High Levelsupporting
confidence: 54%
“…Our data show that even non-activated Tcells are more motile than B-cells. 75 Our study thus underlines a number of previously under-appreciated metabolic distinctions between B-and T-cells that are likely to be of substantial functional relevance in disease microenvironments. Aerobic glycolysis, and not mitochondrial ATP, has been found to be essential for motility in other cell types as well, and has been associated with fluctuations in membrane pump.…”
Section: B-cells In Other Words B-cells Show a Globally High Levelsupporting
confidence: 54%
“…MC-38 is derived from a colorectal (CRC) tumour and has a predominant infiltration of myeloid cells in relation to T and NK cells. 17 MC-38 tumours were modestly sensitive to either checkpoint blockade (αPD-1, αCTLA-4 and αPD-L1) or mTORC1/2 inhibiton as a monotherapy. However significant anti-tumour effects were observed when combining vistusertib and checkpoint blockade (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1 Moreover, another recent study showed that murine cancer cell lines with higher mutational burden (e.g., cell lines derived from carcinogen-induced tumor) respond better to immune-checkpoint therapy than those with lower mutational burdens (e.g., cell lines derived from spontaneous or GEMM-derived tumors). 37 Thus, it is tempting to speculate that GL261-based gliomas are more representative of medium-to-hyper mutant GBM rather than typical low mutational burden (adult) GBM, and hence are more responsive to Figure 6. Anti-PD1 mono-immunotherapy exhibits the highest therapeutic efficacy against preclinical glioma.…”
Section: Discussionmentioning
confidence: 99%